Under close surveillance - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
Marine resources, so crucial to the countries of the South, are being over-exploited. Regulatory measures have been put in place, but must be accompanied by close surveillance of fishing vessels to be effective. Positive examples do exist...